Prevalence and clinical impact of disseminated intravascular coagulation in acute aortic dissection: a nationwide cohort study - Shuhei Murao; Yutaka Umemura; Hirotaka Mori; Yoshinobu Seki; Takayuki Ikezoe; Kohji Okamoto; Satoshi Fujimi; Kazuma Yamakawa (Research and Practice in Thrombosis and Haemostasis)
Background: Acute aortic dissection is a life-threatening cardiovascular emergency with high mortality rates. Disseminated intravascular coagulation (DIC) is a critical complication in patients with acute aortic dissection; however, its incidence and impact on outcomes remain inconclusive. Objectives: This study aimed to evaluate DIC prevalence and prognosis in patients with aortic dissection. Methods: We conducted a multicenter retrospective cohort study using data from the Japan Medical Data Center claims database between 2014 and 2022. DIC was diagnosed based on the criteria of the Japanese Association for Acute Medicine (JAAM-2) and the International Society on Thrombosis and Haemostasis (ISTH). We compared the in-hospital mortality between patients with and without DIC and assessed the impact of coagulopathy using various coagulation profiles. Results: Among the 3037 patients, 40% underwent surgery and 60% did not undergo surgery. The prevalence rates of JAAM-2 DIC and ISTH DIC were 21% and 9.4%, respectively. In-hospital mortality was significantly higher in the DIC group than in the non-DIC group, and this trend was consistently observed in the surgery and nonsurgery groups. Increased DIC scores correlated with higher in-hospital mortality. With the progression of coagulopathy, characterized by thrombocytopenia, elevated prothrombin time-international normalized ratio, prolonged activated partial thromboplastin time, increased D-dimer, and decreased fibrinogen levels, in-hospital mortality also increased. Conclusion: The presence of DIC, as identified by both the JAAM-2 and ISTH criteria, was associated with increased in-hospital mortality in patients with acute aortic dissection. Therefore, further studies are needed to improve the clinical outcomes of these patients.